Clinical application of a fully automated blood collection robot and its assessment of blood collection quality of anticoagulant specimens - Wang, Chong; Gu, Meixiu; Zhu, Jie; Yang, Shuo; Tang, Wenjia; Liu, Zizhong; Pan, Baishen; Wang, Beili; Guo, Wei (Frontiers in Medicine, 2023)
Background and objectives: To investigate the application of intelligent puncture blood collection robots in anticoagulated blood specimens, the satisfaction of subjects with the two blood collection methods, and the feasibility of intelligent blood collection devices to replace manual blood collection methods in clinical work.University were recruited to compare the test results of anticoagulant blood samples between blood collection robot and manual blood collection, a questionnaire was used to inquire about the volunteers' feelings about the two blood collection methods ; the blood collection data of 6,255 patients willing to use the robot for blood collection were collected to analyze the success rate of blood collection.Results: The blood collection robot is superior to manual specimen collection in terms of volume and pain of specimen collection, and the puncture success rate is 94.3%. The anticoagulated blood specimens collected by the robot had 11 indexes statistically different from the results of manual blood collection, but the differences did not affect the clinical diagnosis and prognosis.Conclusions: The intelligent robotic blood collection is less painful and has better acceptance by patients, which can be used for clinical anticoagulated blood specimen collection.